Validation and Cross-cultural Adaptation and Reliability of the Turkish Version of the Michigan Neuropathy Screening Instrument in the Eastern Anatolia Region of Turkey (Annals of Medical Research, 2021)
Aim: Distal symmetric polyneuropathy is a common complication causing foot ulcers and amputations in diabetic patients. The Michigan Neuropathy Screening Instrument (MNSI) is one of the screening methods of diabetic neuropathy, which also provides a comprehensive foot evaluation. The aim of this study was to evaluate the validation, cross-cultural adaptation, and reliability of Turkish Version of the MNSI in the Eastern Anatolia region of Turkey. Materials and Methods: One hundred twenty-six patients with diabetes mellitus were randomly assigned to the study. The questionnaire section of the MNSI was completed by the patients, and the physical examination section was evaluated by health professionals. Nerve conduction studies were performed to 123 patients as the gold standard for diabetic neuropathy. All nerve conduction studies and patients were evaluated by a neurologist. Results: The inter-rater agreement of questionnaire section [ICC: 0.957 (95% CI: 0.940-0.969), p0.001] and physical examination section [ICC: 0.917 (95% CI: 0.884-0.941), p0.001] were excellent. The intra-rater agreement of the questionnaire section [ICC: 0.880 (95% CI: 0.833-0.914), p0.001] and physical examination section [ICC: 0.920 (95% Cl: 0.889-0.943), p0.001] showed a high stability. The area under curve (AUC) for the questionnaire section and physical examination section of the MNSI were 0.588 (p=0.205) and 0.880 (p3, with the sensitivity of 76.2%, specificity of 91.2%, positive predictive value of 64%, negative predictive value of 94.9%.Conclusion: The physical examination section of Turkish version of the MNSI is valid and reliable.
Keywords: Diabetic neuropathy; distal symmetric polyneuropathy; michigan neuropathy screening instrument; nerve conduction study